The Difference in Interleukin-8 (IL-8) on Degrees of Acne Vulgaris Severity - Hendra Tarigan Sibero; Eryati Darwin; Yan Wirasati; Satya Wydya Yenny; Suharmanto (Indian Journal of Forensic Medicine & Toxicology, 2021)
Background: Acne vulgaris (AV) is a follicular disease that occurs most often and affects the area containing sebaceous gland follicles, including the face, back, and body. This is a multifactorial condition. The prevalence of acne vulgaris (AV) is still high both in the world and in Indonesia. As many as 80% of AV is found at the age of 11-30 years and almost 100% in adolescents. Various factors can trigger the onset of AV which can lead to severe complications. Aim: This study looked for the difference in interleukin-8 (IL-8) on degrees of AV severity. Materials and method: This study was an observational analytic study with a crosssectional approach. The research was conducted at the Diniyah Putri Islamic Boarding School, Lampung Province, Indonesia, in August 2020. The independent variable in this study was the AV degree, while the dependent variable was the IL-8 level. The sampling method in this study was consecutive sampling, as many as 63 AV patients. The research material is serum from venous blood. Examination of interleukin-8 levels using the ELISA method. Data analysis was univariate to find the mean and standard deviation of IL-8 levels, as well as the frequency distribution to determine the degree of AV. While the bivariate analysis was to determine the difference in the mean of IL-8 levels in AV patients. Results: The mean of IL-8 levels in AV patients was 38.53. Most of the AV patients are in a severe category. Further analysis found no difference in the mean of IL-8 levels between moderate and severe AV degrees. Conclusion: There was no difference in the mean of IL-8 levels in moderate and severe AV patients, but the IL-8 levels at severe AV degrees were higher than moderate AV degrees.